2015
DOI: 10.1088/0964-1726/24/3/035018
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-responsive shape memory effect in shape memory polyurethane triggered by inductive release of mechanical energy storage undergoing copper (II) chloride migration

Abstract: In this study, 10% weight fraction of copper (II) chloride (CuCl2) was embedded into shape memory polyurethane (SMPU) by dissolving it in a solvent mixture of tetrahydrofuran and N,N-dimethyl formamide. It is found that CuCl2 particles migrate; they are released from the polymer in the water-driven shape recovery process of SMPU composites. SMPU composites, after various immersion times in water, were characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and thermogravime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Emerging trends such as using biodegradable polymers that respond to solvents are gaining interest [97] owing to their excellent biological properties that make them apt for typical biomedical applications. Ten years ago, the use of solvents had widened the avenue to develop stimuli-responsive polymers that can actuate without heat, and we speculate with the introduction of a variety of solvents, and "multi stimuli-responsive properties" shall further evolve this realm of science, thereby developing more robust and versatile shape-changing polymers.…”
Section: Transiting To Solvent Responsive Shape Memory Polymersmentioning
confidence: 99%
“…Emerging trends such as using biodegradable polymers that respond to solvents are gaining interest [97] owing to their excellent biological properties that make them apt for typical biomedical applications. Ten years ago, the use of solvents had widened the avenue to develop stimuli-responsive polymers that can actuate without heat, and we speculate with the introduction of a variety of solvents, and "multi stimuli-responsive properties" shall further evolve this realm of science, thereby developing more robust and versatile shape-changing polymers.…”
Section: Transiting To Solvent Responsive Shape Memory Polymersmentioning
confidence: 99%
“…Recently, Wang et al investigated the water‐induced shape memory effect (SME) in sodium dodecyl sulfate/epoxy composites . Lu et al also reported the chemo‐responsive SME in shape memory polyurethane triggered by inductive release of mechanical energy storage via copper (II) chloride migration . By utilizing the features of thermo/moisture‐responsive SMPs, Sun et al proposed a concept of incorporating micro‐sized devices made of SMPs that were delivered into living cells for surgery or operation .…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be noted that the crystallinity and crystallite size of the recovered SiO 2 /SMPU composite were slightly lower than those of the original states, which indicates that the recovered SiO 2 /SMPU sample does not completely restore to its original shape. This is because the movement and agglomeration of some SiO 2 particles lead the pore walls to be damaged, resulting in crystal loss and a decrease in the crystallinity of the recovered SiO 2 /SMPU composite [ 26 ]. Although the programming process can cause partial damage, it can improve the intermolecular interaction forces to make the SiO 2 /SMPU composites show stronger mechanical properties.…”
Section: Resultsmentioning
confidence: 99%